(untitled) (Research, Society and Development, 2025)
This work investigates renewable energy generation through off-grid photovoltaic systems, focusing on low-power lighting applications. The main objective is to analyze the benefits of using off-grid solar energy through the development of a functional lighting prototype. The specific objectives include: characterizing the system’s operation and main components; identifying advantages and limitations; evaluating its potential under adverse conditions; and estimating the solution’s cost-benefit. The adopted methodology combines a mixed approach, with exploratory and explanatory objectives, utilizing bibliographical and experimental research. The results indicate that the prototype satisfactorily meets the proposed lighting needs, demonstrating efficiency and practical feasibility. It is concluded that off-grid photovoltaic systems promote sustainability and energy independence, providing continuous electricity in remote locations or locations with unstable electrical grids, demonstrating their potential as a reliable and environmentally responsible alternative.